Functional approach and centered-client pratic in rehabilitation of severe Alzheimer disease’s older adult: case report - Cunha, Fabiana Carla Matos da; Cintra, Marco Túlio Gualberto; Cunha, Luciana Cristina Matos da; Silva, Hercília Martins da; Couto, Érica de Araújo Brandão (Revista de Terapia Ocupacional da Universidade de São Paulo, 2011)
Alzheimer's disease (AD) is a degenerative brain disease that affects cognition and perform activities of daily living (ADLs). The treatments available only minimize the cognitive deficits and behavioral changes, being necessary measures to improve the quality of life of patients and caregivers. OBJECTIVES: To present the results of interventions using Ocupational Therapy at home and functional approach focusing on customer conjunction with pharmacological treatment in elderly patients with advanced DA. DESCRIPTION OF THE CASE: A 64 year old male, previously healthy, who in 2004 showed progressive worsening of cognitive function, being diagnosed with probable AD. In 2006 it was assessed by the department of Occupational Therapy (OT), Hospital Socor-BH, showing low scores on cognitive tests and functional (Mini-Mental, Verbal Fluency Test and the Clock; Katz Index, the Canadian Occupational Performance Measure - Time diary and COPM). There is total dependence in ADL, caregiver's great dissatisfaction about the behavioral changes shown and the need for total aid to feed,bath and clothing, plus the disruption of routine occupational. They performed three sessions per week at home, lasting 1 hour and monitored by the neurology and internal medicine. An improvement in the tests after three months of treatment, sustained for 8 months, opposing the developments described in the literature about the inexorable progression of disability. The Katz Index, unlike the time and COPM diary, did not describe the observed qualitative improvement in the performance of ADLs. CONCLUSION: The home of OT intervention related to drug treatment showed significant effects in the case present.